Sociodemographical and clinical profile of intellectual disabled people in a small (Research, Society and Development, 2021)
Intellectual disability (ID) is characterized as a developmental disorder that includes intellectual and adaptive impairments in the conceptual, social and practical domains. Identify the sociodemographic and clinical profile of people with intellectual disabilities in a small city in the interior of Rio Grande do Sul (RS). A census and descriptive study, with a quantitative approach, carried between April and September 2015, through the application of a previously prepared instrument for data collection.  There were 77 people with intellectual disabilities aged between six and 74 years. The majority were male (59.74%), unmarried (92.2%) and illiterate (55.84%). Regarding the diagnosis, 40.25% of the subjects, according to ICD-10, were diagnosed as F79 (Unspecified Mental Retardation), and in 50.64% the diagnosis was given by the neurologist. The study found that most people with intellectual disabilities are in adulthood and are single; their living / health conditions are satisfactory. Although they belong to a small municipality, such data may collaborate with professionals and managers of Health and Education, thus subsidizing discussions aimed at improving the necessary longitudinal care among people with intellectual disabilities.